Immunization in heifers with dual vaccines containing Tritrichomonas foetus and Campylobacter fetus antigens using systemic and mucosal routes - Cobo, Eduardo Ruben (2004)
Vaccines against both bovine venereal campylobacteriosis and trichomonosis were tested. Heifers were assigned to three groups. Groups 1 (n = 21 heifers) and group 2 (n = 20) received a commercial or experimental vaccine, respectively, containing both Campylobacter fetus and Tritrichomonas foetus antigens. Group 3 (n = 21) received adjuvant alone. Preparations were injected SQ in groups 1 and 3 at days -60 and -30 (day 0 was considered the first day of a 90-day breeding period), and in group 2 SQ at days -30 and +11 and into the vaginal submucosa at day -9. Heifers were exposed to two pathogen-infected bulls for 90 days (from day 0 to day +90); furthermore, half of the heifers in each group were challenged at day +39 by an intravaginal instillation of C. fetus venerealis and T. foetus. Pregnancy diagnosis, vaginal culture, and determination of systemic IgG for both organisms were performed. Compared to controls, vaccinated heifers resisted or quickly cleared both pathogens, had a higher pregnancy rate and a higher systemic immune response during and after the breeding period. Overall, the experimental vaccine was superior to the commercial vaccine (groups 2 and 1, respectively). In conclusion, an experimental vaccine containing both C. fetus and T. foetus antigens, given both SQ and intravaginal immediately before breeding and early in the breeding season, yielded superior protection for heifers exposed to bulls harboring C. fetus and T. foetus.